Pengaruh Citra Destinasi Terhadap Minat Berkunjung Kembali Berdasarkan Visit Experience - Aris Sandi Krisna Mulyana; Ari Arisman; Depy Muhamad Pauzy (Global Leadership Organizational Research in Management, 2023)
This research was conducted with the aim of knowing the effect of Destination Image On Interest To Return Based On Visit Experience (Survey of Pangandaran Beach Tourism Visitors). The method used in this study was a survey method using data obtained directly through questionnaires distributed to 165 respondents who were visitors to Pangandaran Beach Tourism. The technique used in this research is path analysis. Based on the results of the research that has been done, it can be seen that, there is a positive and significant influence of Destination Image on Interest in Returning to Pangandaran Beach Tourism. There is a positive and significant influence of Destination Image on Visit Experience in Pangandaran Beach Tourism. There is a positive and significant influence of Visit Experience on Interest in Returning to Pangandaran Beach Tourism, and There is a significant influence of Destination Image on Interest in Returning through Visit Experience on Pangandaran Beach Tourism.